Coleridge’s Late Confessions: Personification, Convention, and Free Agency - King, Joshua (Romanticism and Victorianism on the Net, 2012)
In this essay, I freshly examine Coleridge’s late poems, asking how several respond to his abiding fear of authors and readers surrendering their free wills to the fashions and conditioned attitudes of nineteenth-century print culture. Connecting this anxiety to Coleridge’s views of personification, the Bible, and his own public image, I interpret his late poems as confessions of the conventional determination of writing and reading that he resisted in his critical prose. This late concession, I suggest, might also be an unexpected defense of free agency: by displaying their conventionality, these late poems appear—at least to several early and recent readers—to reflect the strategy of a self-aware and self-determining poet.